Cotton stalk restitution coefficient determination tests based on the binocular high-speed camera technology - Zhang, Bingcheng; Chen, Xuegeng; Liang, Rongqing; Li, Jiali; Wang, Xinzhong; Meng, Hewei; Kan, Za (International Journal of Agricultural and Biological Engineering, 2022)
The restitution coefficient (RC) of cotton stalks is an important elementary physical parameter that is required to establish the crushing mechanical model and research the film residue separation machinery. In this study, the calculation method of restitution coefficient considering the rotation motion of stalk-shaped agricultural materials was derived based on the principle of kinematics and the energy restitution coefficient method, and a test bench for measuring the RC was designed and built. The effects of collision material, moisture content, length, diameter, release height, and collision angle respectively on the RC were investigated by single-factor experiments and orthogonal experiments, and the regression models between influence factors and the RC were established. The results showed that Q235 showed the highest value of the RC, and it was followed by cotton stalks and soil lumps, sequentially. The RC of cotton stalks decreased with the increase of moisture content and diameter, while it increased at first and then decreased with the increase of length. As the release height was less than 500 mm, the RC increased with the increased release height. As the collision angle was less than 40°, the RC showed a linear increasing trend. The significance of the effects of factors on RC decreased with the following sequence: collision angle, length, release height, diameter, and moisture content. Length, collision angle, and release height were extremely significant. The contrast test results showed that the values based on Newton’s restitution coefficient method were smaller than that based on the energy restitution coefficient method. The verification test showed that the predicted rebound height of cotton stalks calculated based on the energy restitution coefficient method was closer to the actual rebound height, and the relative error was less than 5%.Keywords: high-speed camera technology, cotton stalk, collision, restitution coefficient, determination testDOI: 10.25165/j.ijabe.20221504.6370Citation: Zhang B C, Chen X G, Liang R Q, Li J L, Wang X Z, Meng H W, et al. Cotton stalk restitution coefficient determination tests based on the binocular high-speed camera technology. Int J Agric & Biol Eng, 2022; 15(4): 181–189.